Household external finance and consumption - Timothy Besley; Neil Meads; Paolo Surico (Bank of England, External Monetary Policy Committee Unit, 2008)
This paper uses mortgage data to construct a measure of terms on which households access to external finance, and relates it to consumption at both the aggregate and cohort levels. The Household External Finance (HEF) index is based on the spread paid by risky borrowers in the mortgage market. There is evidence that the terms of access to external finance matter more for the consumption of young cohorts in UK data. Results are robust to a wide variety of specifications.
Keywords: D10; E21; G21; 330; external finance; terms of access; household consumption; birth cohorts; pseudo panels; Privater Haushalt; Haushaltsökonomik; Schulden; Hypothek; Risikopräferenz; Konsumentenverhalten; Großbritannien